Pengaruh Penggunaan Fintech Payment dan Financial Knowledge terhadap Financial Management Behavior pada Pelajar Muslim di Yogyakarta - Himatul Muna, Nur; Ismiati, Baiq; Wahyu Wibowo, Febrian; Kamal, Al Haq (Journal of Islamic Economic and Law (JIEL), 2025)
The development of digital financial technology (fintech) has influenced the way students manage their finances, including making payments and daily transactions. However, without adequate financial knowledge, the use of fintech can trigger consumer behavior. Therefore, it is important to examine the extent to which the use of fintech and financial literacy influence financial management behavior among Muslim students. This study aims to examine the influence of Fintech Payment and Financial Knowledge on the Financial Management Behavior of Muslim students in Yogyakarta. The research employed a quantitative approach and utilized a questionnaire as the data collection instrument, with a sample of 100 respondents. Data analysis was conducted using multiple linear regression with SPSS version 22. The results indicate that both Fintech Payment and Financial Knowledge have a significant effect on Financial Management Behavior. These findings emphasize the importance of utilizing financial technology and financial literacy from an early age to foster healthy financial behavior.